Human lumbar spinal column injury criteria from vertical loading at the base: Applications to military environments. (May 2020) - Yoganandan, Narayan; Moore, Jason; DeVogel, Nicholas; Pintar, Frank; Banerjee, Anjishnu; Baisden, Jamie; Zhang, Jiang Yue; Loftis, Kathryn; Barnes, David
Abstract: The objective of this study was to determine force-based lumbar spine injury criteria due to vertical impact using Post Mortem Human Surrogate (PMHS) experiments. Mounted personnel in military vehicles sustain loads from the pelvis in combat events such as underbody blast loadings. Forty-three post mortem human subject thoracolumbar spinal columns were obtained, screened for pre-existing trauma, bone mineral densities (BMDs) were determined, pre-test radiological images were taken, fixed at the ends in polymethylmethacrylate, load cells were attached to the ends of the fixation, positioned on custom vertical accelerator device based on a military-seating posture, and impacted at the base. Posttest images were obtained, and gross dissection was done to confirm injuries, classified into single and multilevel groups, groups A and B. Axial and resultant forces at the thoracolumbar (proximal) and lumbosacral (distal) joints were used as response variables to develop lumbar spine injury risk curves using parametric survival analysis. The Brier score metric was used to rank the variables. Age, BMD, column length, and vertebral body and intervertebral disc areas were used as covariates. The optimal metric describing the underlying response to injury was the distal resultant force for group A and proximal axial force for group B specimens. Force-BMD for group A and force-body area for group B were the best combinations. The IRCs with ±95% confidence intervals and quality of risk curves are given in the paper, and they serve as lumbar spine injury criteria. The present human cadaver Injury Risk Curves (IRCs) can be used to conduct matched pair tests to obtain dummy-based injury assessment risk curves/values to predict injury. The present IRCs can be used in human body finite element models. The relationship between covariates and primary forces presented in this study contribute to a better understanding of the role of demographic, geometric, and material factors to impact acceleration loading.